2017
DOI: 10.1016/j.jid.2016.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Damage Control in a Human (Mini-) Organ: Nrf2 Activation Protects against Oxidative Stress-Induced Hair Growth Inhibition

Abstract: The in situ control of redox insult in human organs is of major clinical relevance, yet remains incompletely understood. Activation of nuclear factor (erythroid-derived 2)-like 2 (Nrf2), the "master regulator" of genes controlling cellular redox homeostasis, is advocated as a therapeutic strategy for diseases with severely impaired redox balance. It remains to be shown whether this strategy is effective in human organs, rather than only in isolated human cell types. We have therefore explored the role of Nrf2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 63 publications
1
73
0
2
Order By: Relevance
“…However, our evidence for a burst of ROS is supported by a recent live‐cell imaging study that detected a more proximally located series of plumes surrounding the hair shaft at the top of the hair bulb . That ROS imbalance creates a toxic environment is well established, but many biological functions may rely upon carefully orchestrated oxidative reactions . We hypothesize an ordered transition from living to dead within the follicle where focal ROS production is a functional step in formation of a strong hair fibre.…”
Section: Discussionsupporting
confidence: 67%
“…However, our evidence for a burst of ROS is supported by a recent live‐cell imaging study that detected a more proximally located series of plumes surrounding the hair shaft at the top of the hair bulb . That ROS imbalance creates a toxic environment is well established, but many biological functions may rely upon carefully orchestrated oxidative reactions . We hypothesize an ordered transition from living to dead within the follicle where focal ROS production is a functional step in formation of a strong hair fibre.…”
Section: Discussionsupporting
confidence: 67%
“…The involvement of a micro‐inflammatory cascade in androgenic alopecia has also been pointed out for years , inflammatory cells surround the permanent region of the follicle producing a damaging environment for stem cells . In addition, in vitro studies showed that oxidative stress reduced hair matrix cell proliferation and increased cell apoptosis . Among the many effects caused by ROS, some are related to a complex biphasic HIF‐1α regulation depending on the intensity and the duration of hypoxia, which could conduct either to an activation or to an inhibition of the ubiquitous HIF‐1α pathway activity .…”
Section: Discussionmentioning
confidence: 99%
“…In order to manipulate the excretory function of HFs, it could be useful to promote human catagen/telogen development. While anagen induction and prolongation by drugs and other agents are an exception in clinical medicine, drug‐induced telogen effluvium is one of the most frequent adverse effects of pharmacological therapy: the vast majority of agents reported to impact on human hair growth actually promotes catagen and thus telogen development (eg Refs ). Luckily, therefore, we are actually quite proficient in the pharmacological induction of catagen/telogen in human HFs and already have a wide repertoire of agents at our disposal for therapeutic exogen induction, that is the promotion of excretory HS shedding.…”
Section: Clinical Perspectivesmentioning
confidence: 99%